Pelatihan Dalam Meningkatkan Skill Berwirausaha Di Seginim Taylor Desa Palak Bengkerung Bengkulu Selatan - Wulandari, Putri Eka; Abi, Yudi Irawan; Desita, Ridha Tri (Universitas Dehasen Bengkulu, 2024)
Sewing skills are skills that involve studying techniques for making clothing and household linen from designing, sewing, to finishing. Sewing skills are one of the important skills in everyday life, because they are related to human needs for clothing. Based on the type of problem studied and its objectives, this research is a qualitative descriptive research. Qualitative descriptive research is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior (Sugiyono, 2019). The reason this research uses a qualitative descriptive approach is because the problems to be discussed are not related to numbers but are described clearly and in detail and obtain in-depth data from training in improving sewing skills in Palak Bengkrung Village, South Bengkulu. Based on research and presentations that have been carried out regarding improving sewing skills in Palak Bengkrung Village, South Bengkulu. The author can provide the following conclusion: The process of improving sewing skills at Seginim Taylor in improving skills has been going well including: the first, namely the preparation stage consisting of determining identification of training needs, preparing programs, preparing experts, preparing facilities, and conducting outreach. Second, the analysis stage is identifying problems. Third, planning, namely by drawing up plans and schedules, carrying out recruitment, then fourth is implementing the sewing training process. The final one is the evaluation or monitoring stage, namely by testing the participant's competency, which will give results after the participant has taken part in the training, whether they are competent or not competent. The result of increasing skills through sewing training is increasing youth skills and increasing knowledge. Sewing training participants can make clothes and design themselves so they can master what they have been taught during the training.